Providing a control method of BTB-VSC Converters under unbalanced faults - Mostafa Abbasi; Mehdi Nafar; Mohsen Simab (Institute of Advanced Engineering and Science, 2022)
Microgrids need control strategies to achieve maximum performance. An appropriate control strategy should have high performance in unbalanced conditions in addition to normal conditions. Today, the use of microgrids, with a variety of power sources, including solar, wind, diesel, energy storage sources to increase the capability of distribution grid has made significant progress. However, controlling and managing their energy in the event of a fault is a challenge that researchers are faced. In this article, two microgrids connected to the grid are studied using a back-to-back (BTB)-voltage source converters (VSC) converter. The results of this research showed that by the usage of above-mentioned convertor first, with power management between microgrids the frequency remains constant in island mode second, they are isolated from each other in terms of faults. The results showed that the use of the proposed method controlled the frequency of two microgrids simultaneously.